FSAUA: A framework for sensitivity analysis and uncertainty assessment in historical and forecasted land use maps. (October 2016) - Tayyebi, Amin; Tayyebi, Amir Hossein; Arsanjani, Jamal Jokar; Moghadam, Hossein Shafizadeh; Omrani, Hichem
Abstract: Land change modelers often create future maps using reference land use map. However, future land use maps may mislead decision-makers, who are often unaware of the sensitivity and the uncertainty in land use maps due to error in data. Since most metrics that communicate uncertainty require using reference land use data to calculate accuracy, the assessment of uncertainty becomes challenging when no reference land use map for future is available. This study aims to develop a new conceptual framework for sensitivity analysis and uncertainty assessment (FSAUA) which compares multiple maps under various data error scenarios. FSAUA performs sensitivity analyses in land use maps using a reference map and assess uncertainty in predicted maps. FSAUA was applied using three well-known land change models (ANN, CART and MARS) in Delhi, India. FSAUA was found to be a practical tool for communicating the uncertainty with end-users who develop reliable planning decisions. Graphical abstract: Highlights: We developed a framework for sensitivity analysis and uncertainty assessment (FSAUA) in land use maps. We applied FSAUA using three well-known land use change models (ANN, CART and MARS). By increasing error in data, suitability values in suitability maps moved towards the maximum uncertainty. By increasing error in data, unstable cells in simulated maps switched from "change" to "no-change" and vice versa. Uncertainty propagated linearly and non-linearly from the suitability risk maps to the simulated risk map.